2020
DOI: 10.1126/scitranslmed.aba8412
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic azetidines kill the diarrheal pathogen Cryptosporidium in mice by inhibiting parasite phenylalanyl-tRNA synthetase

Abstract: Cryptosporidium is a protozoan parasite and a leading cause of diarrheal disease and mortality in young children. Currently, there are no fully effective treatments available to cure infection with this diarrheal pathogen. In this study, we report a broad drug repositioning effort that led to the identification of bicyclic azetidines as a new anticryptosporidial series. Members of this series blocked growth in in vitro culture of three Cryptosporidium parvum isolates with EC50’s in 1% serum of <0.4 to 96 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…This study has served as an example of developing a cure for malaria as well as the potential to give prophylaxis and prevent disease transmission. Additionally, Vinayak et al reported that bicyclic azetidine 32 is a potent inhibitor of Cryptosporidium parvum PheRS (Cp PheRS) for diarrheal disease in young children [48]. The in vivo efficacy of 32 for cryptosporidiosis was shown in immunosuppressed mouse models.…”
Section: Sulfonamido Propanamides and 2-aminopyrimidinesmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has served as an example of developing a cure for malaria as well as the potential to give prophylaxis and prevent disease transmission. Additionally, Vinayak et al reported that bicyclic azetidine 32 is a potent inhibitor of Cryptosporidium parvum PheRS (Cp PheRS) for diarrheal disease in young children [48]. The in vivo efficacy of 32 for cryptosporidiosis was shown in immunosuppressed mouse models.…”
Section: Sulfonamido Propanamides and 2-aminopyrimidinesmentioning
confidence: 99%
“…Two major classes of compounds incorporating tetracyclic tetrahydro-beta-carboline and 4amino-2-piperidone were prepared to selectively inhibit the MetRS of T. brucei. The inhibitory activities of three tetracyclic carboline compounds(47)(48)(49) were tested for the T. brucei MetRS aminoacylation assay, showing submicromolar IC50 values as depicted inFigure 17. One of the tetracyclic compounds exhibited no off-target activity when screened against a panel of 45 CNS proteins.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Phenylalanyl-tRNA synthetase (PheRS) and Lysyl-tRNA synthetase (LysRS) inhibitors with promising activity in several mouse models of infection are also under development (14,33).…”
Section: Introductionmentioning
confidence: 99%